2019
DOI: 10.3390/cells9010036
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a New Platinum-Induced TP53 Mutation in MDAH Ovarian Cancer Cells

Abstract: Platinum-based chemotherapy is the therapy of choice for epithelial ovarian cancer (EOC). Acquired resistance to platinum (PT) is a frequent event that leads to disease progression and predicts poor prognosis. To understand possible mechanisms underlying acquired PT-resistance, we have recently generated and characterized three PT-resistant isogenic EOC cell lines. Here, we more deeply characterize several PT-resistant clones derived from MDAH-2774 cells. We show that, in these cells, the increased PT resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…2e). Next, using these cells in time course analysis of PT response [19][20][21], we evaluated the expression of SFPQ protein during the phases of PT-induced DNA damage and repair. The results showed that higher SFPQ expression in PT-Res cells correlated with decreased and delayed apoptosis and DNA damage response, as evidenced by PARP-1 and caspase-3 cleavage and γ-H2AX expression, respectively ( Fig.…”
Section: Sfpq Expression Increases After Exposure To Ptmentioning
confidence: 99%
“…2e). Next, using these cells in time course analysis of PT response [19][20][21], we evaluated the expression of SFPQ protein during the phases of PT-induced DNA damage and repair. The results showed that higher SFPQ expression in PT-Res cells correlated with decreased and delayed apoptosis and DNA damage response, as evidenced by PARP-1 and caspase-3 cleavage and γ-H2AX expression, respectively ( Fig.…”
Section: Sfpq Expression Increases After Exposure To Ptmentioning
confidence: 99%
“…Additionally, many reports have focused on the p53-dependent anti-cancer effect of natural products [43,[58][59][60][61][62]. Recently, it has been reported that platinum chemotherapy could induce additional mutations in TP53 and further increase platinum resistance in ovarian cancer [63]. In this study, we suggested that p53 was up-regulated and phosphorylated at Ser 15 by PTFSs and played a vital function in intrinsic apoptosis stimulated through PTFSs.…”
Section: Discussionmentioning
confidence: 64%
“…CDDP-resistant cancer cells (referred as Pt-res cells) were generated as previously described and include pooled resistant populations (pool) and individual clones, as indicated in the text [6][7][8].…”
Section: Cell Culture and Cisplatin-resistant Cell Selectionmentioning
confidence: 99%
“…On this regard, we previously generated and characterized three cisplatin (CDDP)-resistant isogenic high grade EOC cell lines (TOV-112D Pt-res, MDAH-2774 Pt-res and OVSAHO Pt-res) from their parental counterparts [6][7][8]. Since gene expression profiling failed to identify signaling pathways commonly altered in Pt-resistant (Pt-res) cells [6], we took advantage of a proteomic approach to investigate the possible mechanisms by which cells acquire CDDP-resistance.…”
Section: Introductionmentioning
confidence: 99%